Ambivalence predicts symptomatology in cognitive-behavioral and narrative therapies: an exploratory study - Braga, Catia (2019)
Background: The identification of poor outcome predictors is essential if we are to prevent therapeutic failure. Ambivalence - defined as a conflictual relationship between two positions of the self: one favoring change and another one favoring problematic stability - has been consistently associated with poor outcomes. However, the precise relationship between ambivalence and clients' symptomatology remains unclear.Objective: This study aims at assessing ambivalence's power to predict symptomatology, using a longitudinal design.Methods: The complete 305 sessions of 16 narrative and cognitive-behavioral cases have been analyzed with the Ambivalence Coding System and outcome measures have been used for each session.Results: Ambivalence emerged as a significant predictor of subsequent symptomatology suggesting that ambivalence is not only related to treatment outcomes, but that it represents a strong predictor of subsequent symptomatology.Discussion: The implications of ambivalence's power to predict outcomes for research and clinical practice are discussed.